Developing Inclusive Education Models to Advance Gender Justice and Social Equity for All Learners - Youssef Abdel Rahman (Nusantara Education, 2025)
This study aims to develop inclusive education models that promote gender justice and social equity for all learners, addressing persistent disparities in access, participation, and outcomes within formal educational settings. This study uses a field-based qualitative approach to explore inclusive education models that advance gender justice and social equity, involving 120 participants selected through purposive and snowball sampling. Data were collected via observation, interviews, and focus group discussions, and were analyzed thematically to identify key patterns, challenges, and effective strategies. The findings reveal that inclusive education is most effective when it integrates gender-sensitive curricula, participatory teaching strategies, and culturally responsive pedagogy that recognizes students’ diverse backgrounds and learning needs. Structural factors, such as policy support, teacher training, and school leadership, significantly influence the implementation of inclusive practices. Additionally, the study identifies gaps in awareness and resource allocation, highlighting the need for systemic reforms to ensure equitable learning opportunities. Innovative practices, such as peer mentoring, adaptive learning technologies, and community engagement programs, demonstrate measurable improvements in students’ academic performance, self-efficacy, and social inclusion. This research contributes to the field of education by offering a practical, evidence-based framework for designing and implementing inclusive education models that simultaneously advance gender justice and social equity. By providing actionable strategies and highlighting contextual challenges, the study informs policymakers, educators, and stakeholders in crafting interventions that promote equitable participation and learning outcomes. The findings underscore the critical role of intersectional approaches in addressing systemic inequalities and fostering environments where all learners, regardless of gender, socioeconomic status, or ability, can thrive.